Analysis of Scientific Literacy Research in Indonesia as A Basis for Developing Ecotourism-Based Teaching Materials: Literature Review - Hamidi, Hamidi; Purwoko, Agus Abhi; Harjono, Ahmad; Al Idrus, Agil; Rokhmat, Joni; Sukarso, AA. (Balai Publikasi Indonesia, 2024)
Science and technology have an important role in facing educational challenges in the 21st century, so that science education, which is part of education, has an important role in preparing students to have scientific literacy. The aim of this research is to determine research trends regarding scientific literacy as a basis for developing ecotourism-based teaching lessons for junior high school students on Lombok Island. The study in writing this article used literature studies or literature reviews from several previous studies published in Scopus indexed journals or proceedings from 2017-2022. The 157 articles obtained were selected into 30 articles. Literature analysis and synthesis was carried out using bibliometric analysis with the VosViewer application. The research results show that a lot of research on scientific literacy has been carried out in Indonesia, and one of the research related to scientific literacy is the development of teaching materials because the development of teaching materials has quite a big influence in increasing students' scientific literacy. However, there is still no research on the development of ecotourism-based teaching materials in increasing students' scientific literacy in Indonesia, so research on this topic is important to do